Initial study on SARS-CoV-2 main protease inhibition mechanism of some potential drugs using molecular docking simulation - Quan, Pham Minh; Huong, Le Thi Thuy; Toan, Tran Quoc; Tung, Ngo Son; Dan, Nguyen Trong; Thuy, Tran Thi Thu; Cuong, Nguyen Manh; Long, Pham Quoc (Vietnam Journal of Science and Technology, 2020)
The infection by the new coronavirus SARS-CoV-2 (called as COVID-19 disease) is a worldwide emergency, however, there is no antiviral treatment or vaccine until now. The crystal structure of SARS-CoV-2 main protease has been made publicity in the Protein Data Bank recently. Many efforts have been conducted by scientists including the use of several commercial medicines, however, understanding at atomic level how these compounds prevent SARS-CoV-2 protease is still lacking. In this context docking protocol was employed to rapidly estimate the binding affinity and binding pose of six drugs on the main protease.